The Influence of the form Error after Rotor Manufacturing on the Output Characteristics of an Orbital Hydraulic Motor - Panchenko, Anatolii; Панченко, Анатолій Іванович; Панченко, Анатолий Иванович; Voloshyna, Anzhela; Волошина, Анжела Анатоліївна; Волошина, Анжела Анатольевна; Milaieva, Iryna; Мілаєва, Ірина Іванівна; Милаева, Ирина Ивановна; Panchenko, Ihor; Панченко, Игорь Анатольевич; Панченко, Ігор Анатолійович; et al. (My University, 2018)
The technology of rotors manufacturing for orbital hydraulic motors causes a certain form error of the gear surface. This leads to oscillations of the diametrical gap between the rotors. Such oscillations have a negative effect on the change in the output characteristics of the orbital motor. The previous studies on the issue consider the interaction between the rotors of orbital hydraulic machines as a gapless (theoretical) connection. The authors do not take into account that between the rotors of the orbital hydraulic motor, there is no rigid kinematic connection. This allows the internal rotor to move randomly within the diametrical gap (self-aligning). The study led to the development of the mathematical models that describe the relationship between the design features of the rotors and the output characteristics of an orbital hydraulic motor. To simulate the oscillation of the diametrical gap, the limiting deviations for the form error of the rotor gear surfaces have been substantiated. Investigations revealed that fluctuations in the form error of the rotor gear surface have a significant effect on the variation of the diametrical gap. The limiting deviations in the form errors of the gear surface manufacturing enabled to eliminate the oscillation of the diametrical gap and to ensure stability of the output characteristics for the orbital hydraulic motor
Keywords: form error after rotor manufacturing; orbital hydraulic motor